The Humanization of Education: Some Major Contemporary Challenges for an Innovative Concept - Golz, Reinhard; Graumann, Olga; Whybra, David (International Dialogues on Education Journal, 2019)
The humanities and social sciences, and in particular the educational sciences, are facing major challenges in view of the current socio-political, economic and foreign policy upheavals. The authors characterize some of these challenges to education theorists and practical pedagogues against the background of the ideas of a “Humanization of Education” that emerged in Russia after the collapse of the Soviet Union and led to the founding of the “International Academy for the Humanization of Education” (IAHE) in 1995. That humanization approach is still very relevant today. Here, the focus is on the current discussions of national identity, individuality and social responsibility, problems and tasks of inclusion and integration, as well as on the effects of digitalization on personality development. The influence of “Progressive Education” in the first half of the 20th century on the discussions centering on the “Humanization of Education” is taken into account, and the authors pose the question of the sustainability of such innovations in times of social upheavals.